2011
DOI: 10.1002/ejsp.803
|View full text |Cite
|
Sign up to set email alerts
|

Concern for self‐image and social image in the management of moral failure: Rethinking shame

Abstract: Moral failure is thought to damage self-image when people appraise it as indicating a global self-defect. This appraisal is thought to be associated with the feeling of shame and thus self-defensive motivation. However, a damaged social image better explains self-defensive motivation to hide from and avoid others. Based on an integrative review of theory and research, we offer a conceptual model of how concern for self-image and social image guides the experience of moral failure. The model distinguishes the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
355
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(405 citation statements)
references
References 52 publications
(137 reference statements)
38
355
2
7
Order By: Relevance
“…Indeed, empirical research has repeatedly demonstrated shame to be able to induce prosocial behaviours, such as donating, cooperating, or gift giving, notably in situations where people are together with others towards whom they feel ashamed (De Hooge, 2014;De Hooge, Breugelmans, & Zeelenberg, 2008). Similar findings have been reported for experiences of group-based shame (Gausel & Leach, 2011;Gausel, Leach, Vignoles, & Brown, 2012;Welten et al, 2012). Taken together, current research on the behavioural effects of shame suggests that shame leads to both social withdrawal and social approach.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Indeed, empirical research has repeatedly demonstrated shame to be able to induce prosocial behaviours, such as donating, cooperating, or gift giving, notably in situations where people are together with others towards whom they feel ashamed (De Hooge, 2014;De Hooge, Breugelmans, & Zeelenberg, 2008). Similar findings have been reported for experiences of group-based shame (Gausel & Leach, 2011;Gausel, Leach, Vignoles, & Brown, 2012;Welten et al, 2012). Taken together, current research on the behavioural effects of shame suggests that shame leads to both social withdrawal and social approach.…”
supporting
confidence: 69%
“…Haidt, 2003;Keltner & Harker, 1998;Lewis, 1971Lewis, , 1992Tangney, 1991), others argue that shame motivates social approach (e.g. De Hooge et al, 2008;Gausel & Leach, 2011;Gausel et al, 2012;Welten et al, 2012). Surprisingly, no empirical research thus far directly compared these two opposing expectations, because existing studies did not include the possibility for respondents to choose between entering social and non-social situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aristotle (trans. 1985) therefore admitted that in order to act morally most people need self-control and guidance that is provided not only by their subjective sense of shame (see also, Gausel & Leach, 2011), but also by socially imposed rules, standards and obligations. In a modern western society, people are likely to hold moral values like; benevolence, respect for the autonomy of others, respect for others' rights, and civil courage (even though they sometimes fail to respect these values).…”
Section: Aristotle's Anti-hedonismmentioning
confidence: 99%